Design and optimization of the seed conveying system for belt-type high-speed corn seed guiding device - Li, Yifei; Zhou, Wenqi; Ma, Chengcheng; Feng, Zhaohua; Wang, Jinwu; Yi, Shujuan; Wang, Song (International Journal of Agricultural and Biological Engineering, 2024)
Seeding is an important part of improving corn yield. Currently, seed guide tubes are mostly used as transportdevices. But the existing seed guide tubes cannot meet the requirements or achieve the goal of fixing the seed falling trajectory.A seed collision phenomenon occurs occasionally. So, in response to the problems that the seeds and seed guide tube collide orbounce under high speed operation, which results in a lower sowing qualification rate and poor spacing uniformity, a seedreceiving and conveying system comprising a belt-type high-speed corn seed guiding device was designed and optimized, tomeet the needs of high-speed precision sowing operations and improve the spacing uniformity.The factors affecting the seedconveying performance were obtained by analyzing the mechanical properties of the seeds at various movement stages. Thesefactors were the number of seed cavities between adjacent seeds, the forward speed, the height from the ground, and theinstallation angle. Single factor simulation experiments were conducted by selecting the paddle spacing as the test factor andusing the pass rate, reseeding rate, omission rate and coefficient of variation as the evaluation indexes to investigate theinfluence of the paddle spacing on the seed guide performance of the device and further determine the structural parameters ofthe paddle belt. Orthogonal rotation combination tests of three factors and five levels were also conducted through benchtesting.Then the test outcomes were optimized. The results indicated that the best results were obtained when the number ofseed cavity intervals between adjacent seeds was 5.16, the installation angle was 79.40°, and the height from the ground was31.84 mm. At this time, the qualified rate was 98.49%, the repeated sowing rate was 0.48%, the missed sowing rate was 1.03%,and the coefficient of variation was 6.80%. Experiments were used to validate the optimization results, and all of the obtainedindex data satisfied the criteria for accurate and quick corn sowing. The study’s findings can serve as a theoretical foundationfor a belt-type high-speed corn seed guiding device optimization test.Keywords: corn, high-speed sowing, belt-type seed guide device, testDOI: 10.25165/j.ijabe.20241702.8427Citation: Li Y F, Zhou W Q, Ma C C, Feng Z H, Wang J W, Yi S J, et al. Design and optimization of the seed conveying systemfor belt-type high-speed corn seed guiding device. Int J Agric & Biol Eng, 2024; 17(2): 123–131